A novel two-terminal-pair pulse-driven Josephson impedance bridge linking a 10 nF capacitance standard to the quantized Hall resistance. (15th February 2017) - Bauer, S; Behr, R; Hagen, T; Kieler, O; Lee, J; Palafox, L; Schurr, J
Abstract: In this paper the realization of a two-terminal-pair impedance bridge based on pulse-driven Josephson arrays will be presented. This bridge was used to link a 10 nF capacitance standard to the quantized Hall resistance at 1233 Hz. With pulse-driven Josephson arrays the setup for a quadrature bridge can be reduced dramatically. For the combination of the AC quantum Hall resistance and a 10 nF capacitance standard, most of the uncertainties caused by contact resistances in a two-terminal-pair definition were circumvented by a triple-series connection of the AC quantum Hall resistance. The capacitance value obtained by the new Josephson impedance bridge was compared to the results from a transformer-based ratio bridge and agrees within 1.3 parts in 10 8 . Sources of systematic uncertainties were investigated and the combined relative uncertainty of the bridge was determined to be less than 1 × 10 − 8 ( k = 1) and 13.9 nF F −1 ( k = 1) for the link of the 10 nF capacitance standard.